2020
DOI: 10.1038/s41467-019-14127-9
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic endothelial cells prime naïve CD8+ T cells into memory cells under steady-state conditions

Abstract: Lymphatic endothelial cells (LECs) chemoattract naïve T cells and promote their survival in the lymph nodes, and can cross-present antigens to naïve CD8 + T cells to drive their proliferation despite lacking key costimulatory molecules. However, the functional consequence of LEC priming of CD8 + T cells is unknown. Here, we show that while many proliferating LECeducated T cells enter early apoptosis, the remainders comprise a long-lived memory subset, with transcriptional, metabolic, and phenotypic features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 85 publications
(133 reference statements)
1
44
0
Order By: Relevance
“…Recently, LECs have been shown to generate antigen-experienced T cells with memory-like function that can rapidly evolve effector functions upon pro-inflammatory stimulation. These results give first insights into the functional consequence of LEC-associated T cell priming ( Vokali et al, 2020 ).…”
Section: Tecs and Their Immunoregulatory Propertiesmentioning
confidence: 84%
“…Recently, LECs have been shown to generate antigen-experienced T cells with memory-like function that can rapidly evolve effector functions upon pro-inflammatory stimulation. These results give first insights into the functional consequence of LEC-associated T cell priming ( Vokali et al, 2020 ).…”
Section: Tecs and Their Immunoregulatory Propertiesmentioning
confidence: 84%
“…The steady-state conditions have been considered as synonymous with an induction and maintenance of immune tolerance ( Iberg and Hawiger, 2020a ; Iberg et al, 2017 ; Steinman et al, 2003 ). However, T cells with effector and memory phenotype and functions can paradoxically also arise under minimal perturbations of homeostasis ( Huang et al, 2003 ; Kawabe et al, 2017 ; Long et al, 2007 ; Vokali et al, 2020 ). It remains unclear how autoimmune and other effector responses can be initiated despite the presence of mechanisms that induce and maintain T cell tolerance in the steady state ( ElTanbouly et al, 2020 ; Iberg and Hawiger, 2020a ; Iberg et al, 2017 ; Vokali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms linked to mLV dysfunction can contribute to the modulation of the neuro-immune response. For instance, lymphatic vessels play a direct role in the maturation of T cells ( 65 , 66 ), and dysfunction of the lymphatics leads to the persistence of immune cells and mediators in tissues, resulting in a chronic inflammation and tissue damage ( 67 ). Moreover, recent papers reported that the VEGFR-3 signaling, promoting lymphangiogenesis, is also important to both initiate the acute innate and adaptive immune responses and to regulate the chronic T cell-mediated response (by changing the Treg/Th2 balance), suggesting an immunomodulatory role for this signaling ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%